Animal Traction : A Selected Bibliography - Goe, Michael R.; Hailu, Michael; International Livestock Centre for Africa (Addis Ababa, Ethiopia : Documentation Centre, International Livestock Centre for Africa, 1983)
This bibliography is an attempt to provide a comprehensive listing of documents that relate to the research or application of animal traction. It is hoped that it will be a useful tool to individuals working in areas of agricultural research and extension, national government and development agencies, and planning and administrative positions.
"February 1983."
Includes indexes.
ne 9/04/2018
Loans
Keywords: Draft Animals; Animal Traction